Fostering A Culture Of Responsibility: Engaging Nurses In Equipment Care And Maintenance (Journal of Namibian Studies : History Politics Culture, 2022)
This paper explores the crucial role of nurses in equipment care and maintenance within healthcare settings, emphasizing the importance of fostering a culture of responsibility among nursing staff. By actively engaging nurses in equipment management, healthcare institutions can enhance patient safety, operational efficiency, and cost-effectiveness.